An improved method for solubilisation of wool keratin using peracetic acid. Issue 2 (April 2017) - Shavandi, Amin; Carne, Alan; Bekhit, Adnan A.; Bekhit, Alaa El-Din A.
Abstract: Keratin in wool is a potentially important natural source of protein with many applications. However, solubilisation of keratin from wool is challenging. The yield of solubilised keratin was investigated using peracetic acid (PA) treatment of wool. The yield of keratin obtained by extraction of wool with various concentrations of PA (6, 12, 24 and 36%) with 1, 2, or 3 days of treatment time was examined. Treatment of wool for two days with 24% PA was found to be the optimum treatment condition, resulting in a 57% yield of water soluble keratin (WSK) and a 40% yield of insoluble keratin (ISK). The physicochemical properties of the obtained keratin samples were determined using XRD, FTIR and SDS-PAGE. FTIR analysis of the WSK and ISK showed both extracts had a high content of cysteine- S -sulfonated residues and SDS-PAGE confirmed that the extracts contained proteins in the 40–60 kDa molecular weight range.